Konstruksi Realitas Makam Dewi Sekardadu dalam Komunikasi Pariwisata Pro-Poor di Sidoarjo - Didik Hariyanto; Djarot Meidi Budi Utomo; Hendra Sukmana; Ferry Adhi Dharma (Fakultas Ilmu Komunikasi UKWMS, 2020)
This study aims to determine the construction of reality carried out by the community against the tomb of Dewi Sekardadu as pro-poor tourism development. This research method is qualitative with the Peter L. Berger phenomenological approach. The results showed that there was a construction of reality carried out through three stages (externalization, objectivation, internalization). In the externalization, the stakeholders emphasized the Islamic side of Dewi Sekardadu. The objective reality of Dewi Sekardadu as an Islamic figure was accepted by the whole community because they got primary socialization from the family. Secondary socialization of Dewi Sekardau's tomb as a tourism commodity occurs when the community is mature. Due to a lack of knowledge, existing tourism support facilities cannot be maximized by most people. They still work as keepers of fish ponds and river fishermen due to the lack of socialization and training in tourism management from the government.